2022
DOI: 10.1007/s10787-022-01078-9
|View full text |Cite
|
Sign up to set email alerts
|

Is sitagliptin effective for SARS-CoV-2 infection: false or true prophecy?

Abstract: Coronavirus disease 2019 (Covid-19) is caused by severe acute respiratory syndrome type 2 (SARS-CoV-2). Covid-19 is characterized by hyperinflammation, oxidative stress, and multi-organ injury (MOI) such as acute lung injury (ALI) and acute respiratory distress syndrome (ARDS). Covid-19 is mainly presented with respiratory manifestations; however, extra-pulmonary manifestations may also occur. Extra-pulmonary manifestations of Covid-19 are numerous including: neurological, cardiovascular, renal, endocrine, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…It was (Nadwa et al 2022 ) demonstrated that SIRT1 activation by resveratrol was mediated and dependent on the activity of lamin A protein. Dysregulation of lamin A protein attenuates PGC1-α/NAD with subsequent reduction of SIRT1 activity and development of mitochondrial dysfunction (Alomair et al 2022 ). These verdicts indicated that lamin A protein plays a crucial role in SIRT1 expression and activation.…”
Section: Role Of Sirt1 Activators In Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…It was (Nadwa et al 2022 ) demonstrated that SIRT1 activation by resveratrol was mediated and dependent on the activity of lamin A protein. Dysregulation of lamin A protein attenuates PGC1-α/NAD with subsequent reduction of SIRT1 activity and development of mitochondrial dysfunction (Alomair et al 2022 ). These verdicts indicated that lamin A protein plays a crucial role in SIRT1 expression and activation.…”
Section: Role Of Sirt1 Activators In Pdmentioning
confidence: 99%
“…Lamin protein is the only nuclear protein expressed in the CNS, essential for neuronal differentiation and survival. Lamin A protein is critical for lifespan through inhibition of neurodegeneration (Alomair et al 2022 ). It has been reported that mutation with reduced expression of lamin A protein was linked with the development of aging-related degenerative brain disease including PD.…”
Section: Role Of Sirt1 Activators In Pdmentioning
confidence: 99%
“…The levels of soluble DPP4 (sDPP4) levels were increased in patients with acute and chronic viral infections; thus, the concentration of sDPP4 might be useful as a biomarker for these diseases ( 74 ). DPP4 inhibitors (e.g., gliptins) could be beneficial for patients with COVID-19, probably through interference with viral invasion ( 74 ) and activation of inflammatory pathways ( 75 ).…”
Section: Discussionmentioning
confidence: 99%
“…COVID‐19 pandemics around the world are primarily caused by SARS‐CoV‐2 infections, and the clinical presentation can range from asymptomatic to mild upper respiratory tract infections or severe lung injury. SARS‐CoV‐2 infection induces a cytokine storm (CS) leading to the release of proinflammatory cytokines, such as interleukin (IL)−6, IL‐1β, and tumor necrosis factor (TNF)‐α, which play an important role in the progression of COVID‐19, and the mechanism is mainly related to the interaction between SARS‐CoV‐2 and immune cells 26,27 . According to research, COVID‐19 severity and clinical prognosis are strongly linked to CS 28 …”
Section: Discussionmentioning
confidence: 99%